GC-MS analysis, toxicological and oral glucose tolerance assessments of methanolic leaf extract of Eucalyptus globulus - Bamidele Stephen Ajilore; Tolulope Olamide Oluwadairo; Olubukola Sinbad Olorunnisola; Olumide Samuel Fadahunsi; Peter Ifeoluwa Adegbola (SpringerOpen, 2021)
Abstract Background Eucalyptus globulus leaf has shown promising potential in its efficacy to manage some diseases but little is known about its safety and its use in the management of diabetes. This study was designed to identify the bioactive compounds present in Eucalyptus globulus leaf extract (EGLEX), assess its toxic effects and its oral glucose tolerance ability. Powdered Eucalyptus globulus leaf was extracted with methanol using standard extraction procedure. Preliminary phytochemistry, gas chromatography-mass spectrometry (GCMS) analysis of the extract, its acute and subacute toxic effects and on its glucose tolerance (in-vivo) capability were assessed using standard laboratory techniques. Results EGLEX was tested positive for the presence of alkaloids, cardiac glycosides, flavonoids, tannins, phlobatannins and terpenoids. Nine compounds were identified by GCMS analysis of the leaf extract. EGLEX (up to 300 mg/kg bwt) showed no toxicity in all the rats dosed for the period of 14 days. The histomorphological study of the liver and kidney tissues harvested from rats dosed with 2000 mg/kg bwt showed features of histoarchitectural distortions in the two tissues. EGLEX (200 mg/kg bwt) further demonstrated effective glucose utilization as insulin and metformin. Conclusions The results obtained deduced that EGLEX is safe at a lower dose of 300 mg/kg bwt but toxic at higher dose of 2000 mg/kg bwt, and that single dose (200 mg/kg bwt) of the plant extract prevented hyperglycemia in normal rats.